2017
DOI: 10.1002/smj.2724
|View full text |Cite
|
Sign up to set email alerts
|

Toward a social practice theory of relational competing

Abstract: Research Summary: This article brings together the competitive dynamics and strategy-as-practice literatures to investigate relational competition. Drawing on a global ethnography of the reinsurance market, we develop the concept of micro-competitions, which are the focus of competitors' everyday competitive practices. We find variation in relational or rivalrous competition by individual competitors across the phases of a micro-competition, between competitors within a micro-competition, and across multiple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 129 publications
(318 reference statements)
0
60
0
Order By: Relevance
“…In particular, by demonstrating the bounded space of local managers or the local involvement of other individuals, practice offers a nuanced view on localization in EMF internationalization (Bjerregaard & Klitmoller, 2016). For instance, as social structures and shared meanings are transmitted through practice, mutually understood and agreed-upon practices help individuals create group cohesion and communications to recognize local concerns and manage differences (Jarzabkowski & Bednarek, 2018;Wenger, 1998).…”
Section: Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, by demonstrating the bounded space of local managers or the local involvement of other individuals, practice offers a nuanced view on localization in EMF internationalization (Bjerregaard & Klitmoller, 2016). For instance, as social structures and shared meanings are transmitted through practice, mutually understood and agreed-upon practices help individuals create group cohesion and communications to recognize local concerns and manage differences (Jarzabkowski & Bednarek, 2018;Wenger, 1998).…”
Section: Practicementioning
confidence: 99%
“…In sum, by focusing on explaining social phenomena in a processual way as accomplished locally by reflexive actors, the dimension of practice contributes to a geographic relational approach in terms of the questions it asks and the answers it provides (Jarzabkowski & Bednarek, 2018;Jones, 2014). Understanding practice requires both qualitative and quantitative analysis (Lounsbury & Crumley, 2007).…”
Section: Practicementioning
confidence: 99%
See 1 more Smart Citation
“…To provide a framework to explore Instagram as a micro practice of interactive value formation, we draw on practice theory to drive the current research. The interactive value formation at the provider-customer interface has been studied from the theoretical lens of practice-theory perspective (see Echeverri & Skålén, 2011;Jarzabkowski & Bednarek, 2018;Makkonen, Olkkonen, & Halinen, 2012;Perera, Anger, & Klein, 2018). In this paper, as Shove (2004), Perera et al, (2018), Ropke (2009) have argued practice theory can be applied to understand environmental consumption, we apply practice theory to the understanding of internationalization of SME exports via Instagram usage.…”
Section: Contemporary Management Research 81mentioning
confidence: 99%
“…Organizational studies of markets have produced accounts of market construction that focus either on how calculative tools are involved in market making (Giamporcaro & Gond, 2016; Poon, 2009) or on how multiple actors’ relational practices influence the competitive dynamics (Jarzabkowski & Bednarek, 2018) or social structure of markets (McKague, Zietsma, & Oliver, 2015). Although these studies have shown that both toolmaking (Callon, 1998; Fourcade, 2007) and organizational practices (Ahrne, Aspers, & Brunsson, 2015) play a role in market making, scholars have rarely cross-fertilized insights from these two streams of studies.…”
mentioning
confidence: 99%